The Phenomenon of Language Mixing Used among Gen Z in Indonesian Students - Ishak Ishak; Desri Arwen; Euis Yanah Mulyanah (STAI Hubbulwathan Duri, 2025)
Code-mixing has become increasingly prevalent among Generation Z, particularly in academic and social contexts. This study explored the types of code-mixing used by 8th-semester Gen Z students at Muhammadiyah University of Tangerang, Indonesia, and examined the underlying reasons for this linguistic phenomenon. A qualitative descriptive approach was employed. Data were collected through direct observation of students’ spoken interactions and open-ended interviews conducted at different times. Audio recordings of code-mixing utterances were documented and transcribed for analysis. A total of 177 code-mixing utterances were identified, consisting of three types: insertion (85.3%, 151 instances), alternation (14.7%, 26 instances), and congruent lexicalization (6.2%, 11 instances). The data suggest that insertion is the most dominant form of code-mixing among participants. Several reasons were identified for the frequent use of code-mixing. Students often engage in it unconsciously and see it as a way to improve their English language skills. Additionally, code-mixing is perceived to carry social prestige, making speakers feel confident, proud, and